Popularna kultura in regresivni populizem - Luthar, Breda (Teorija in praksa, 2021)
On both the individual and collective levels, society has a constant tendency to observe itself through elites. I understand the practice of celebrification and the ubiquity of local celebrity culture as an important justification narrative that plays a vital role in the post-socialist neoliberal consensus. This analysis addresses the way Melania Trump is popularly represented in Slovenian media and argues that this involves the entanglement of celebrity discourse and practice of celebrification in commercial media culture with regressive populism. The celebrity discourse is an important discursive practice in the legitimation of the existing class relations and redistribution of public wealth after socialism. As a cultural repertoire of "proto-national" sentiments, it can be organised to support right-wing populism
Keywords: celebrifikacija; Celebrities in mass media; celebrity; class; Mass media; Melania Trump; Melanija Trump; Množični mediji; neoliberalism; neoliberalizem; online social networks; political discourse; politični diskurz; populism; populizem; postsocialism; postsocializem; regresivni populizem; regressive populism; Slavni ljudje v medijih; slavnost; spletna družbena omrežja; Trump, Melania